Buying and Selling Broker: The Management and Islamic View - Damirah, Damirah; Shalilah, Mar’atun; Iryanto, Rivaldo Kurniawan; Alaaraj, Hassan (Universitas Islam Negeri Raden Intan Lampung, 2023)
The rise of intermediaries in buying and selling transactions, where the seller uses another person to sell the goods, and vice versa, the buyer hires someone to look for goods to buy. However, in several facts on the ground, there were still irregularities that caused losses to both parties. This study aims to find out and understand the samsarah or broker contract in car buying and selling transactions at the Showroom Kab. bones. This research is a qualitative method with data collection through interviews, observation, and documentation. The results of the study show that samsarah contracts, which refer to transactions that use the services of people as an exchange, include samsarah contracts, which in Islamic fiqh can take the form of brokers, distributors, agents, and so on. The practice of buying and selling used car dealers or samsarah by Showroom in Kab. Bone in general fulfills the principles of honesty, transparency, and responsibility. The owner of the goods being sold will pay the intermediary by giving the broker permission to increase the selling price. According to scholars, buying and selling through intermediaries is legal as long as all parties benefit including sellers, buyers, and intermediaries, then this type of intermediary business is permissible. However, this business activity must carry out payment transactions through Islamic banks so that they run perfectly according to Islamic principles.